Foraminifera Distribution Patterns within Sequence Stratigraphy (A Case Study: Blora Area and Surroundings/Low Latitude Area) - Khoiril Anwar M. (Institute for Research and Community Services (LPPM) ITB, 1998)
Sari. Analisis stratigrafi sikuen memerlukan data yang menyeluruh dari berbagai disiplin ilmu geologi, termasuk biostratigrafi. Secara hipotesis, biostratigrafi (foraminifera) dapat dijadikan alat untuk mengidentifikasi sikuen. Studi kasus di daerah lintang rendah telah dilakukan dan beberapa parameter seperti asosiasi biofasies, bioevent, kelimpahan, serta keragaman dan komposisi fauna telah dicoba diterapkan untuk mencari pola atau karakteristik tertentu yang dapat dijadikan alat untuk mengidentifikasi sikuen. Peran biostratigrafi foraminifera sebagai alat dalam interpretasi sikuen tampaknya dipengaruhi oleh lingkungan tempat endapan sedimen ditemukan. Pada endapan laut dangkal, meskipun resolusi umur kurang baik, batas sikuen, komponen sikuen, dan beberapa horizon dalam sikuen akan lebih dapat dikenali dari pola sebaran foraminiferanya sebaliknya, pada laut dalam, meskipun resolusi umur akan lebih baik, unsur lain kurang terlihat dengan baik, kecuali bidang condensed section yang berasosiasi dengan maximum flooding surface. Foraminifera Distribution Patterns within Sequence Stratigraphy (A Case Study: Blora Area and Surroundings/Low Latitude Area)Abstract. The approach in sequence stratigraphy analysis needs data from multi-discipline including biostratigraphy. Hypothetically, it indicates that biostratigraphy (foraminifera) can be used as a tool to identify a sequence. A case study at low latitude area has been done and some parameters such as microfauna assemblage, bioevent, abundance, diversity, and fauna composition have been applied to find some characteristics which could be used as a tool to identify sequence stratigraphy. Biostratigraphy as a tool seems to be influenced by the environment where the sediments are deposited. In shallow marine, where the age resolution is not very good, the sequence boundary and maximum flooding surface (MFS) are still easy to identify. On the contrary, in deep marine setting, biostratigraphy can be used to date the age and identify the condensed section which is associated with maximum flooding surface (MFS).